Saving newborn lives in rural communities: learning from the BRAC experience - Hadi, Abdullahel; Ahmed, Munir (BRAC Research and Evaluation Division (RED), 2019)
SNL study is a pilot project of BRAC to improve the health of the newborn in two sub-districts in Bangladesh. Neonatal mortality -- major health crisis in the poor countries -- has gripped poor countries for many years. This problem has been compounded by a lack of health care resources and poverty. The neonatal mortality has been very high in Bangladesh. Policy makers are therefore seeking ways to reduce illness and prevent deaths by improving neonatal care in the home and at local health facilities. Method SNL project has two service delivery strategies tb improve the health of the neonates. The operations research (OR) design includes a comparison area for each of the two delivery strategies. All women living in the study areas, who gave birth were identified and included in this study. The data were collection for this study continued from March 2004 - March 2005. The data collection includes several steps: identification of pregnant women, antenatal interview before two weeks of the delivery, interview at 48 hours after delivery and follow-up interviews after four weeks of delivery. Outcomes The outcome measures include changes in patterns of home care, health practices and referral. Other outcomes included estimates of neonatal mortality and illness. The study also generated a body of information on the process of introducing such an intervention in communities, and on the programme experiences with planning and participation. Lessons Learned The SNL initiative demonstrates that safe delivery and essential newborn care can be strengthened at the community level. Short duration of programme implementation is unlikely to produce visible changes and, thereby, to reach to any credible conclusions. Not all improvements are likely to sustain in the absence of continuity of the efforts. The programme design and implementation plan could have been more realistic than it has been.